Exploring different imaging techniques for non-invasive monitoring of insect population: a review article - M. A., Najib; A. M. S., Rashid; A., Ishak; M., Ramle; A. H., Izhal (Association of Agricultural Technology in Southeast Asia, 2024)
An accurate technique of monitoring insect pest populations is very crucial in crop protection. Traditionally, this is achieved by manual detection of infested area and manual counting of the target species. However, it is a time-consuming task that might be useless if the target species has migrated after the resultant manual counting. Thus, this paper attempted to explore and discuss the imaging systems developed in recent years for monitoring, detecting, and counting insect pest populations in various infested areas, and the advancements made around the world. The developed systems were structured into standalone systems, network-based imaging systems, and Red, Green and Blue (RGB) vision and thermographic imaging. Recent trends show that standalone and networked imaging systems are the most prominent technologies in insect detection and counting for industry adoption. Standalone and networking imaging technologies each possess distinct characteristics and can be employed to monitor insect pest populations according to the user's needs and preferences. In all these systems, robustness of the camera setup is critical because it dictates the accuracy of detection for a particular target species. From both research and commercialization standpoints, there is needed for further exploration of imaging technology in insect pest detection and counting. The aim is to streamline traditional labor-intensive and costly methods.